A novel DLG4 variant causes DLG4-related synaptopathy with intellectual regression - Sachi Tokunaga; Hideki Shimomura; Naoko Taniguchi; Kumiko Yanagi; Tadashi Kaname; Nobuhiko Okamoto; Yasuhiro Takeshima (Human Genome Variation)
Abstract DLG4-related synaptopathy is a neurodevelopmental disorder caused by a DLG4 variant. We identified a novel de novo heterozygous frameshift variant, NM_001321075.3(DLG4):c.554_563del, in a Japanese girl. Intellectual regression without motor delay was observed at 2 years of age, and she was diagnosed with autism spectrum disorder and attention-deficit/hyperactivity disorder. Recognizing the possibility of DLG4-related synaptopathy in patients with intellectual regression is important for ensuring an accurate diagnosis.